Modulation of SOD1 Subcellular Localization by Transfection with Wild- or Mutant-type SOD1 in Primary Neuron and Astrocyte Cultures from ALS Mice - Lee, Do-Yeon; Jeon, Gye Sun; Shim, Yu-mi; Seong, Seung-Yong; Lee, Kwang-Woo; Sung, Jung-Joon (Experimental neurobiology, 2015)
Amyotrophic lateral sclerosis (ALS) is a fatal neurological disorder characterized by selective degeneration of motor neurons. Mutant superoxide dismutase 1 (SOD1) is often found as aggregates in the cytoplasm in motor neurons of various mouse models and familial ALS patients. The interplay between motor neurons and astrocytes is crucial for disease outcome, but the mechanisms underlying this phenomenon remain unknown. In this study, we investigated whether transient transfection with wild-type and mutant-type SOD1 may lead to amplification of mutant SOD1-mediated toxicity in cortical neurons and astrocytes derived from wild-type and mutant-type (human G93A-SOD1) mice. In transgenic mice expressing either wild- or mutant-type SOD1, we found that green fluorescent protein (GFP)-wtSOD1 was present in the cytoplasm and nuclei of wild-type cortical neurons and astrocytes, whereas GFP-mutant SOD1 was mainly cytoplasmic in wild- and mutant-type cortical neurons and astrocytes. These findings indicate that intracellular propagation of misfolding of GFP-wt or mtSOD1 are possible mediators of toxic processes involved in initiating mislocalization and aggregation. Here, we provide evidence that cytoplasmic aggregates induce apoptosis in G93A-SOD1 mouse cortical neurons and astrocytes and that the toxicity of mutant SOD1 in astrocytes is similar to the pathological effects of ALS on neurons in vitro. Collectively, our results indicate that mtSOD1 probably interacts with wtSOD1 via an unknown mechanism to produce augmented toxicity and may influence aggregate formation and apoptosis.